To simplify the expression \(-\frac{3}{4}r + 3 - \frac{5}{6}r - 6\), we can follow these steps:
-
Combine like terms:
- Combine the \(r\) terms: \(-\frac{3}{4}r - \frac{5}{6}r\)
- Combine the constant terms: \(3 - 6\)
-
Let's first simplify the constant terms: \[ 3 - 6 = -3 \]
-
For the \(r\) terms, we need a common denominator to combine \(-\frac{3}{4}r\) and \(-\frac{5}{6}r\). The least common multiple of 4 and 6 is 12.
Converting each term: \[ -\frac{3}{4}r = -\frac{3 \times 3}{4 \times 3}r = -\frac{9}{12}r \] \[ -\frac{5}{6}r = -\frac{5 \times 2}{6 \times 2}r = -\frac{10}{12}r \]
-
Now combine the \(r\) terms: \[ -\frac{9}{12}r - \frac{10}{12}r = -\frac{19}{12}r \]
-
Putting it all together, we have: \[ -\frac{19}{12}r - 3 \]
Therefore, the simplified expression is: \[ -\frac{19}{12}r - 3 \]